Thermodynamic and Kinetic Investigation of the Adsorption and Desorption of Trimethoprim and Its Main Metabolites in Mediterranean Crop Soils - Carmen Mejías; Juan Luis Santos; Julia Martín; Irene Aparicio; Esteban Alonso (Molecules, 2023)
The adsorption–desorption processes of organic pollutants into the soil are one of the main factors influencing their potential environmental risks and distribution in the environment. In the present work, the adsorption–desorption behavior of an antibiotic, trimethoprim (TMP), and two of its main metabolites, 3-desmethyltrimethoprim (DM-TMP) and 4-hydroxytrimethoprim (OH-TMP), were assessed in three Mediterranean agricultural soils with different physicochemical characteristics. Results showed that the adsorption kinetic is performed in two steps: external sorption and intraparticle diffusion. The adsorptions of the studied compounds in soils were similar and fitted to the three models but were better fitted to a linear model. In the case of DM-TMP and OH-TMP, their adsorptions were positively correlated with the soil organic matter. In addition, desorption was higher in less organic matter soil (from 1.3 to 30.9%). Furthermore, the desorptions measured for the TMP metabolites were lower than those measured in the case of TMP (from 2.0 and 4.0% for OH-TMP and DM-TMP, respectively, to 9.0% for TMP).